Active Management of Third Stage of Labour: Conventional Versus International Federation of Gynaecology & Obstetrics (FIGO) Guidelines in A Resource Poor Setting - FARUKH BASHIR, FATIMA SHEHZAD, RIZWANA NAZ (Journal of Fatima Jinnah Medical University, 2018)
Objective: To compare the efficacy of AMTSL of FIGO/ICM guidelines with conventional management of third stage of labour in terms of maternal morbidity in resource poor setting of tertiary hospital. Methodology: It was a Quasi Experimental Study The study was conducted in Gynecology Unit-III, Sandeman province Hospital, Quetta. Six months from 01-11-2007 to 05-02-2008 then From 06-05-2008 to 01-07-2008.Total 200 labouring women after gestational period of 28 weeks till 41 weeks having spontaneous labour or augmented labor. 100 women were managed conservatively and 100 women managed by FIGO guideline. Two hundred women recruited from the labour room. Hundred women were managed conventionally. Hundred women were managed by FIGO guideline. Data was compiled, transfer and analyzed accordingly through SPSS version 12.0. Results: As compared to group A, in group B the risk of PPH, need of blood transfusion was significantly high and there was significant reduction in haemoglobin percentage after delivery in group B as compared to group A. Other side affects like headache, nausea, vomiting are also higher in group B as compared with group A with further risk of elevation of systolic blood pressure in group B. Conclusion: It is concluded that FIGO guidelines of AMTSL are more efficacious in prevention of PPH. The conventional method of third stage of labour with minimal side effects can safely be administered to hypertensive patients